Perceptions of Learning and Stages of Concern Among Graduates of a Native Teacher Education Program - Duquette, Cheryll (Alberta Journal of Educational Research, 2003)
The purpose of this study was to examine the learning outcomes of students who had recently completed a two-year community-based Native Teacher Education Program (NTEP). The participants were 22 graduates of an NTEP who responded to open-ended items in a questionnaire on what they had learned throughout the program. Four women also participated in a focus group. The learning of the graduates was grouped according to the categories found in a previously developed framework: curriculum planning and evaluation, discipline and classroom management, pupils and pupil-teacher interactions, and the profession of teaching (Duquette & Cook, 1999). It was found that the NTEP graduates learned the most in the first three areas of the framework. As well, those with more than five years of experience working in the schools learned more in the pupils and pupil-teacher interactions category than their less experienced peers. The learning as stated by all the graduates showed that they addressed self-survival and impact concerns as described by Fuller (1969). The major source of their learning was through observation of their supervising teachers.